Study protocol for a randomized, double-blind, placebo-controlled trial of a single preoperative steroid dose to prevent nausea and vomiting after thyroidectomy: the tPONV study - Tarantino, Ignazio; Beutner, Ulrich; Kolb, Walter; Müller, Sascha A.; Lüthi, Cornelia; Lüthi, Andreas; Schmied, Bruno; Clerici, Thomas; Warschkow, René (BMC anesthesiology, 2013)
Postoperative nausea and vomiting after general anesthesia is not only an unpleasant problem affecting 20-30% of surgical patients but may also lead to severe postoperative complications. There is a particularly high incidence of postoperative nausea and vomiting following thyroidectomy. Dexamethasone has been described as highly effective against chemotherapy-induced nausea and vomiting and has been proposed as a first-line method of postoperative nausea and vomiting prophylaxis. Despite this possible beneficial effect, the prophylactic administration of dexamethasone before surgery to prevent or ameliorate postoperative nausea and vomiting has not been established. A bilateral superficial cervical plexus block during thyroid surgery under general anesthesia significantly reduces pain. Of even greater clinical importance, this block prevents the need for postoperative opioids. Therefore, patients undergoing thyroidectomy and a bilateral superficial cervical plexus block are an ideal group to investigate the efficacy of dexamethasone for postoperative nausea and vomiting. These patients have a high incidence of postoperative nausea and vomiting and do not require opioids. They have no abdominal surgery, which can cause nausea and vomiting via a paralytic ileus. Combined with the highly standardized anesthesia protocol in use at our institution, this setting allows all known biases to be controlled.